2023
DOI: 10.1021/acs.macromol.3c00488
|View full text |Cite
|
Sign up to set email alerts
|

Rheo-NMR at the Phase Transition of Liquid Crystalline Poly-γ-benzyl-l-glutamate: Phase Kinetics and a Valuable Tool for the Measurement of Residual Dipolar Couplings

Fabian Hoffmann,
Karel Kouřil,
Stefan T. Berger
et al.

Abstract: Using a home-built rheo-NMR apparatus with Couette geometry that allows pulse program-controlled switching of spinning speeds, the formation of liquid crystalline phases of poly-γ-benzyl-l-glutamate (PBLG) in CDCl3 is studied at concentrations up to 15% (w/v) using deuterium NMR of the solvent under static and shear force conditions. A tilt of director alignment from 0 to ≈75–79° is observed. While the well-known first-order phase transition from isotropic to the liquid crystalline phase is detected in the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…Sugase et al built mechanical shear unit into conventional cryogenic probe and investigated the aggregation process of proteins, amyotrophic lateral sclerosis-related superoxide dismutase 1 (SOD1). High-resolution Rheo-NMR can in situ capture the transient events of fibrillation at the molecular level, revealing the coexistence of folded and unfolded SOD1 . Luy et al recently revealed the influence of temperature, concentration, and shear rate on the phase transition behaviors of liquid crystalline poly-γ-benzyl- l -glutamate (PBLG) under shear by 2 H Rheo-NMR . All the above results clearly show the power of Rheo-NMR for studying complicated phase transition under flow conditions and tensile deformation mechanism of various materials at the molecular level.…”
Section: Rheo-nmrmentioning
confidence: 99%
“…Sugase et al built mechanical shear unit into conventional cryogenic probe and investigated the aggregation process of proteins, amyotrophic lateral sclerosis-related superoxide dismutase 1 (SOD1). High-resolution Rheo-NMR can in situ capture the transient events of fibrillation at the molecular level, revealing the coexistence of folded and unfolded SOD1 . Luy et al recently revealed the influence of temperature, concentration, and shear rate on the phase transition behaviors of liquid crystalline poly-γ-benzyl- l -glutamate (PBLG) under shear by 2 H Rheo-NMR . All the above results clearly show the power of Rheo-NMR for studying complicated phase transition under flow conditions and tensile deformation mechanism of various materials at the molecular level.…”
Section: Rheo-nmrmentioning
confidence: 99%